2010
DOI: 10.1093/eurheartj/ehq167
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs are new and sensitive biomarkers of myocardial infarction

Abstract: AimsCirculating microRNAs (miRNAs) may represent a novel class of biomarkers; therefore, we examined whether acute myocardial infarction (MI) modulates miRNAs plasma levels in humans and mice.Methods and resultsHealthy donors (n = 17) and patients (n = 33) with acute ST-segment elevation MI (STEMI) were evaluated. In one cohort (n = 25), the first plasma sample was obtained 517 ± 309 min after the onset of MI symptoms and after coronary reperfusion with percutaneous coronary intervention (PCI); miR-1, -133a, -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
657
6
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(702 citation statements)
references
References 36 publications
34
657
6
5
Order By: Relevance
“…13,21,22 In line with previous evidence, the results of massively parallel sequencing in our study showed that miR-499-5p, miR133a, and miR-208b were elevated >2-fold in patients with AMI when compared with controls ( Figure 2). However, the increase of miR-208a did not reach the threshold of 2-fold change (data are not shown).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…13,21,22 In line with previous evidence, the results of massively parallel sequencing in our study showed that miR-499-5p, miR133a, and miR-208b were elevated >2-fold in patients with AMI when compared with controls ( Figure 2). However, the increase of miR-208a did not reach the threshold of 2-fold change (data are not shown).…”
Section: Discussionsupporting
confidence: 91%
“…However, the increase of miR-208a did not reach the threshold of 2-fold change (data are not shown). D'Alessandra et al 21 were unable to detect an elevation in circulating miR-208a levels after AMI AMI indicates acute myocardial infarction; CI, confidence interval; miRNA, microRNA; and OR, odds ratio. *The relative expression level of miRNAs was normalized to cel-miR-39 and calculated by 2 -ΔCt .…”
Section: Discussionmentioning
confidence: 99%
“…There was an increase of more than 1,000-fold in acute myocardial infarction 6,[37][38][39] of miRs-208b and-499. In this condition, they reflect tissue injury and cell death.…”
Section: Microrna As Biomarker In Heart Failurementioning
confidence: 96%
“…It regulates the expression of the beta myosin heavy chain, resulting in the enhancement of myocardial oxygen metabolism and tolerance (24). It has also been demonstrated that the expression levels of miR-499 exhibit a significant change in certain heart diseases, including AMI (25,26).…”
Section: Plasma Levels Of Mir208b (A) and Mir499 (B) Were Significantmentioning
confidence: 99%